Corporate Social Responsibility, Intellectual Capital Disclosure, Dan Risiko Bisnis Terhadap Nilai Perusahaan - Sadenah Berlin; Dirvi Surya Abbas; Imam Hidayat (Jurnal Akuntan Publik, 2023)
The purpose of this study was to determine the effect of Corporate Social Responsibility, Intellectual Capital Disclosure, and Business Risk on Firm Value variable in mining sector manufacturing companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 5 years, namely 2017-2021. The population in this study includes mining sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2021 with a sampling technique that uses purposive sampling. The type of data used is secondary data obtained from the official website of the IDX and the company. The data analysis technique used is panel data regression. The results of the study stated that Corporate Social Responsibility and Intellectual Capital Disclosure had an effect on firm value.